Pemanfaatan Material Lokal Dan Produk Samping Industri Sebagai Agregat Batu Pecah Dan Filler terrhadap Kinerja Marshall pada Campuran Panas Aspal Beton Lapis Permukaan Aus (ACWC) - Asmaroni, Dedy; Irwanto, Taurina Jemmy (Universitas Dr. Soetomo, 2019)
The use of ACWC asphalt as a surface layer in Madura continues to increase as traffic growth increases following the opening of the Suramadu Bridge. In addition to having the advantages of stability in accepting loads compared to other types of surface layers, ACWC asphalt is also easily made and carried out in the field. However, asphalt mixing plant (AMP) companies in Madura still use materials from outside Madura as coarse aggregates such as river breaking stones and fly ash and cement used as fillers to improve stability. Based on this, this research was carried out by utilizing local meter which has the same properties in the form of local Madura crushed stone which will be used as coarse aggregate and industrial by-products in the form of rice husk ash (by-product of brick industry) and limestone powder (limestone mining byproducts ) used as filler. For this purpose samples were made with the percentage of filler used was 2%, 4%, 6%, 8% and 10%. Marshall test testing includes calculation of density, flow, VMA, VIM, VFB, and stability. From the test results, AC-WC uses local materials with both types of filler, namely Limestone and Rice Husk Ash. There is one type of mixture that meets the Marshall characteristics, namely the use of local materials and filler of limestone 8% asphalt variation 6.5%. With a value of 2,285 Density, 1,852,863 kg Stability, Flow 3,467 mm, Marshall Quotient 534,48 kg / mm, VIM 3,058%, V.M.A 15,941%, VFB 80,819%. While the local material and fillers of Rice Husk Ash from the results of Marshall Test for Flow, VIM, and VFB did not meet the requirements so that the use of rice husk ash filler could not be used as a substitute for cement.